Mission-Oriented Innovation Policy for Sustainable Development: A Systematic Literature Review - Odeh Al-Jayyousi (16937040) (2023)
This paper aims to explore effective ways to incorporate a mission-orientated framework to innovation policies that are designed to achieve the United Nations’ Sustainable Development Goals (SDGs). This paper aims to identify the strategies of MOIP to inform innovation and sustainability in the Middle East and North Africa (MENA) region, particularly focusing on the Gulf Corporation Council (GCC) context. It does so through a systematic literature review of current studies related to MOIP, according to the PRISMA protocol, regarding countries in the GCC region that are currently undergoing ambitious national strategic development plans with sustainability and inclusive growth at their core. This particularly targets SDG 9, which is about fostering innovation that is inclusive and sustainable. Implications for this study may inform innovation policy in the GCC and even inspire the wider Middle East and North Africa (MENA) region in terms of innovation metrics, energy transitions, the innovation ecosystem, public participation, and policy implementation and evaluation. Based on the systematic review and current innovation ecosystems and practices in the GCC, recommendations and strategic options are outlined. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su151713101